Analisa Key Performance Index Salesman Pada PT Mega Buana Indah - Wahana Mandikova; Santi Oktavianti; Teguh Iman Santoso (Universitas Sumatera Selatan, 2022)
ABSTRACT Knowledge and skills of human resources which come from organization or companies are intangible asset that will be a competitive asset to companies, and will create a positive value for the company. Effectively managing employee’s performance is one of key factor to increase the company business performance. Effectively managing performance includes measurement process of employee’s output objectively through a series of exact performance indicators. This research discussing about key performance index salesman in PT Mega Buana Indah, which is consist of 6 indicators that is first impressions, needs assessment, communicated product knowledge, interpersonal presentation, product recommendations, sales and closing tactics. Data is collected by distributing questionnaire as much as the determined samples. The result of this research concludes that each indicator has affecting the key performance index salesman.